Unconventional Protein Secretion in Brain Tumors Biology: Enlightening the Mechanisms for Tumor Survival and Progression - Iglesia, Rebeca Piatniczka; Prado, Mariana Brandão; Alves, Rodrigo Nunes; Escobar, Maria Isabel Melo; Fernandes, Camila Felix de Lima; Fortes, Ailine Cibele dos Santos; Souza, Maria Clara da Silva; Boccacino, Jacqueline Marcia; Cangiano, Giovanni; Soares, Samuel Ribeiro; Araújo, João Pedro Alves de; Tiek, Deanna Marie; et al. (Frontiers in Cell and Developmental Biology, 2022)
Non-canonical secretion pathways, collectively known as unconventional protein secretion (UPS), are alternative secretory mechanisms usually associated with stress-inducing conditions. UPS allows proteins that lack a signal peptide to be secreted, avoiding the conventional endoplasmic reticulum-Golgi complex secretory pathway. Molecules that generally rely on the canonical pathway to be secreted may also use the Golgi bypass, one of the unconventional routes, to reach the extracellular space. UPS studies have been increasingly growing in the literature, including its implication in the biology of several diseases. Intercellular communication between brain tumor cells and the tumor microenvironment is orchestrated by various molecules, including canonical and non-canonical secreted proteins that modulate tumor growth, proliferation, and invasion. Adult brain tumors such as gliomas, which are aggressive and fatal cancers with a dismal prognosis, could exploit UPS mechanisms to communicate with their microenvironment. Herein, we provide functional insights into the UPS machinery in the context of tumor biology, with a particular focus on the secreted proteins by alternative routes as key regulators in the maintenance of brain tumors.